Is it hyperfibrinolysis or fibrinolytic shutdown in severe COVID-19?. Issue 210 (February 2022) - Nielsen, Nathan D.; Rollins-Raval, Marian A.; Raval, Jay S.; Thachil, Jecko
Highlights: Understanding of the disorders of coagulation/fibrinolysis associated with COVID-19 is lacking. D-dimer levels have been demonstrated to be consistently elevated in the setting of COVID-19. These D-dimer elevations are found even in the absence of VTE or systemic hyperfibrinolysis. COVID-19 patients have depressed systemic fibrinolysis and resistance to exogenous fibrinolytics. This paradox may be due to tissue level hyperfibrinolysis but insufficient systemic fibrinolysis.